Changing Epidemiology of Invasive Mold Infections in Patients Receiving Azole Prophylaxis. (12th February 2017) - Lamoth, Frederic; Chung, Shimin J.; Damonti, Lauro; Alexander, Barbara D.
Abstract: Breakthrough invasive mold infections (IMIs) that occur during posaconazole or voriconazole prophylaxis are rare complications for which epidemiological data are lacking. This retrospective analysis comparing 24 microbiologically documented breakthrough with 66 nonbreakthrough IMIs shows a shift towards non- Aspergillus molds with a significantly increased proportion of rare multidrug-resistant molds.